2016
DOI: 10.1017/gov.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Economic Intimidation in Contemporary Elections: Evidence from Romania and Bulgaria

Abstract: This article examines electoral intimidation of voters at their workplace in contemporary new democracies. What is the relative importance of workplace intimidation in the broader portfolio of clientelistic strategies used by politicians at times of elections? What explains the subnational variation in the incidence of this electoral strategy? We answer these questions using empirical evidence from two East European countries – Romania and Bulgaria. We assess the prevalence of non-programmatic electoral mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Similar logics have been forwarded for Lebanese (Corstange 2017) and Nicaraguan (González-Ocantos et al 2015) respondents. Beyond the possible association with low socioeconomic standing, respondents may wish to avoid being seen as a participant in an immoral or unethical behavior (Mares, Muntean, and Petrova 2018) or to "acknowledge that the handout influenced their vote" (Brusco, Nazareno, and Stokes 2004, 69). Respondents may also wish to avoid appearing to have violated perceived social norms about behavior as a democratic citizen (Kramon 2016).…”
Section: Clientelism In Developing Countriesmentioning
confidence: 99%
“…Similar logics have been forwarded for Lebanese (Corstange 2017) and Nicaraguan (González-Ocantos et al 2015) respondents. Beyond the possible association with low socioeconomic standing, respondents may wish to avoid being seen as a participant in an immoral or unethical behavior (Mares, Muntean, and Petrova 2018) or to "acknowledge that the handout influenced their vote" (Brusco, Nazareno, and Stokes 2004, 69). Respondents may also wish to avoid appearing to have violated perceived social norms about behavior as a democratic citizen (Kramon 2016).…”
Section: Clientelism In Developing Countriesmentioning
confidence: 99%
“…3 Another possible strategy is the provision of political services by government officials in exchange for political support. 4 In other electoral contexts, politicians do not seek to influence the choices made by voters at the ballot box through vote-buying or patronage, but through electoral intimidation. Electoral intimidation includes the use of threats directed against voters that support "undesired" political candidates and post-electoral reprisals directed against these voters.…”
Section: Isabela Mares and Boliang Zhumentioning
confidence: 99%
“…28 Thus, it is plausible that firms involved in quarrying may mobilise local votes and influence for their political sponsors in exchange for licenses. Indeed, previous studies from Romania and Bulgaria have found evidence of electoral intimidation in the workplace (Mares et al, 2016).…”
Section: Results By License Typementioning
confidence: 97%